Al Makmun's Liberal Thoughts in Understanding the Quran as a Mahkluk - Muhammad Nasir (Jurnal Ar Ro'is Mandalika (Armada), 2021)
The study of science plays a very significant role in the Islamic thought scene. Many schools of each school have different characteristics in explaining a concept; The Qur'an, for example, is understood differently depending on the school it follows. The Mu'tazilites as one of the schools that had a very wide influence with reason as the initial basis of their thought. Many of the mu'tazilite schools spawned pioneers who brought about a change in the paradigm of thinking, especially related to the concept of the new Qur'an. Al-makmum in this case very strongly states that the Qur'an is something created and is new. In 212 AH, Al-Makmun stated explicitly that the Qur'an is a creature, in addition to his saying that Ali ibn Abi Talib was superior to Abu Bakr and Umar ibn Khattab. Almost these highly controversial remarks caused great disaster among the Muslims. As it turned out, the people were very sensitive to the issues they considered an important part of the religion. Almost all scholars in the time of Al-Makmun were tested on the creation of the Qur'an. Scholars who agree with the teachings of the creation of the Qur'an will be free from the torment of Al- Makmun. On the contrary, scholars who dispute and disagree with the doctrine receive undeserved treatment for scholars. For example, Imam Ahmad bin Hanbal was one of the victims of the inquisition (mihnah) who had felt the narrowness of the prison and the weight of the handcuff chains he once inhabited and bound him. Months in prison, yet all the suffering could not change Al-Ma'mun's understanding of the status of the Qur'an. Until his death, Imam Ahmad continued to say that the Qur'an was kalamullah.